Transforming Poverty-Related Policy with Intersectionality. (September 2016) - Corus, Canan; Saatcioglu, Bige; Kaufman-Scarborough, Carol; Blocker, Christopher P.; Upadhyaya, Shikha; Appau, Samuelson
Despite progress toward poverty alleviation, policy making still lags in thinking about how individuals experience poverty as overlapping sources of disadvantage. Using the lens of intersectionality, this article identifies the gaps that arise from a conventional focus on isolated facets of poverty. Insights generated from an analysis of extant scholarship are used to develop a road map to help policy makers develop programs that address the complex experience of poverty and promote transformative solutions.